Factors That Influence Student’s Decisions In Choosing Universitas Mikroskil - Tya Wildana Hapsari Lubis; Nasrul Efendi; Suci Pertiwi; Djoni (Jurnal Ekonomi, 2024)
This research aims to determine the factors influencing students' decisions in choosing Mikroskil University. This type of research is associative with a quantitative approach. The variables used in this study to measure students' decisions are service quality, promotion, and facilities of the university. The number of samples used in this research is 310 respondents, namely students from all study programs at Mikroskil University using the probability sampling method with a proportional stratified random sampling approach. From the adjusted R-square value, a value of 0.785 is obtained, which when multiplied by 100 yields 78.500 per cent. This indicates that the contribution of each independent variable to influence the dependent variable is 78.500 per cent, meaning that the variables of service quality, promotion, and university facilities contribute 78.500 per cent to students' decision variables in choosing Mikroskil University, while the remaining 21.500 per cent is influenced by other variables beyond the scope of this research.